2014
DOI: 10.1177/0161734613519602
|View full text |Cite
|
Sign up to set email alerts
|

Contrast in Intracardiac Acoustic Radiation Force Impulse Images of Radiofrequency Ablation Lesions

Abstract: We have previously shown that intracardiac acoustic radiation force impulse (ARFI) imaging visualizes tissue stiffness changes caused by radiofrequency ablation (RFA). The objectives of this in vivo study were to (1) quantify measured ARFI-induced displacements in RFA lesion and unablated myocardium and (2) calculate the lesion contrast (C) and contrast-to-noise ratio (CNR) in two-dimensional ARFI and conventional intracardiac echo images. In eight canine subjects, an ARFI imaging-electroanatomical mapping sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Also, recent studies have concluded that current methods of MRI assessment of atrial RFA lesions show limited resolution for characterizing small gaps in an ablation line . Intracardiac ARFI imaging provides higher spatial resolution (sub‐millimeter) than current MRI methods …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Also, recent studies have concluded that current methods of MRI assessment of atrial RFA lesions show limited resolution for characterizing small gaps in an ablation line . Intracardiac ARFI imaging provides higher spatial resolution (sub‐millimeter) than current MRI methods …”
Section: Discussionsupporting
confidence: 68%
“…RFA induced tissue heating causes irreversible thermocoagulation of intracellular and contractile proteins, which in turn reduces tissue viscoelasticity . Although RFA does not produce long lasting detectable tissue changes in standard 2‐D ultrasound images, it has been previously shown that ARFI imaging identifies discrete stiff regions that coincide with pathological RFA lesions both in vitro , and when imaging during diastole in vivo using animal models , . Further, in several of these in vivo studies, ARFI imaging was implemented using conventional intracardiac echocardiography (ICE) imaging catheters and clinically available cardiac ablation mapping systems, and regions with “gaps” in the ablation line as identified with ARFI imaging were correlated with intact conduction …”
Section: Introductionmentioning
confidence: 99%
“…The measured ARFI‐induced displacement magnitude is inversely proportional to tissue stiffness and presents a representation of the relative stiffness . We have previously shown in vitro that ARFI imaging can visualize RFA lesions, and that in vivo intracardiac echocardiography (ICE) based diastolic ARFI imaging can provide high‐contrast visualization of stiff atrial lesions consistent with electrical block at the imaging site . Initial results from a clinical feasibility study demonstrated that ARFI imaging could identify stiffness changes consistent with RF ablation in human patients …”
Section: Introductionmentioning
confidence: 99%
“…However, in these previous studies, atrial function in ablated patients was measured after several months follow-up whereas in this study strains are measured several minutes to hours before, during and after ablation. Eyerly et al investigated the change of acoustic radiation force induced displacement of myocardial tissue with ICE in canines during an RF ablation [24, 50]. They reported that displacements in ablated sites were inferior to displacement in unablated sites.…”
Section: Discussionmentioning
confidence: 99%